The Palestinians’ Quest For Justice At The ICJ: The Unsc As A Stumbling Block? - Fareed Mohd Hassan; Nurul Azyani Zafirah Sabaruddin; Aryuni Yuliantiningsih; Muhammad Rusli Arafat; Belardo Prasetya Mega Jaya (Faculty of Law, Brawijaya University, 2024)
Non-Indexed Publication